Models in approaching Higher-Order Thinking Skills (HOTS) towards the Malaysian Labor Market / Nurin Farzana Mohamad Fadzil and Nurul Hidayana Mohd Noor - Mohamad Fadzil, Nurin Farzana; Mohd Noor, Nurul Hidayana (2021)
In this era of globalization, employability skills are pivotal in the labor market that can help the graduates or entry-level in attracting the employer and organization. One of the main focuses of skill is the ability in higher-order thinking skills (HOTS) which is the important component viewed by the organization in recruiting the graduates especially for those who have the ability in problem-solving since it will give benefits to the organization (Saad & Majid, 2014). In Malaysia, higher thinking skills be measured through the ability on translating, analyzing and manipulating information (Wilson & Narasuman, 2020). Hence, the value of higher thinking skills must be adapted among the graduates since studies in higher institutions. This can be supported during the pandemic of Covid 19, a study determined there is a significant effect between the academic background with the agreement on impacts of the Covid 19 towards graduate employability (Iqmal et al., 2020). However, the graduates are affected to be employed during this pandemic especially for those who are not proactive in upgrading their knowledge and skills (Hayati et al., 2020). In addition, in the labor market graduates are not proactive in upgrading skills (Hayati et al., 2020) which this kind of issue existed due to no alignment of practices of higher thinking skills with the policy of the skills provided (Chun & Abdullah, 2019). Therefore, some models (i.e, Bloom's Taxonomy, FRISCO Model, Watson-Glaser Critical Thinking Skill, and RED Model) will be focused on and this study also is to aim at the best model that can be used in approaching the higher-order thinking skills (HOTS) towards the Malaysian Labor Market. Thus, the purpose of this study is to identify the best model of the higher order thinking skills (HOTS) which can be used in the teaching and learning process by following the suitable models that could help the students be more criticized in thinking and solving problems.